Fungsi Perencanaan Pembangunan Desa Di Kecamatan Siau Timur Kabupaten Siau Tagulandang Biaro (Sitaro) - AWUMBAS, HEIN OKTAVIAN; Rompas, Sonny; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTThe study aims to determine the function of development planning Siau In District East VillageDistrict Sitaro. This study was conducted by researchers in the district of East Siau Sitaro District, asDistrict of East Siau has the largest population in the area of greatest as well as the character of a pluralisticsociety. Siau sub-district consists of 16 Village / Sub.Researchers using qualitative approach in conducting this study, it can be seen from the proceduresapplied, the procedure that produces descriptive data; greeting; or writing and observable behavior ofpeople (subject) itself.Based on the formulation of the problem the focus of this research is the function Planning RuralDevelopment in Sub Siau East District Sitaro with variable observations include: (a) construction, utilizationand maintenance of infrastructure and environmental Village, (b) construction, utilization and maintenanceof health infrastructure, (c ) Health services Village, (d) construction, utilization and maintenance offacilities and infrastructure of education and culture, (e) Development of productive economic activities aswell as the development, utilization and maintenance of facilities and economic infrastructure, (f) protectionof the environment, (g) of Development civic, (h) Community Development Division.Based on the research results it can be concluded that of all the villages in the district of East Siau hasmade RPJMDesa that has been poured into the village of Regulation respectively, that have gone through thestages of Musdus, village workshops, Musrenbang And Post Musrenbang, based on democratic principles.Keywords: Plan, The Development Village.